1985
DOI: 10.1111/j.1365-2621.1985.tb10461.x
|View full text |Cite
|
Sign up to set email alerts
|

Forces Involved in Soy Protein Gelation: Effects of Various Reagents on the Formation, Hardness and Solubility of Heat‐Induced Gels Made from 7S, 11S, and Soy Isolate

Abstract: The effects of various reagents on the formation, hardness and solubility of heat-induced gels of soybean 7S, 11s globulins and isolate were studied. Gels were formed in 30 mM Tris HCI buffer (pH 8.0) with or without reagents by heating at 80°C for 30 min. The results indicated that electrostatic interactions and disulfide bonds are involved in the formation of 1 IS globulin gels; mostly hydrogen bonding in 7s globulin gels and hydrogen bonding and hydrophobic interactions in soy isolate gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
0
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(157 citation statements)
references
References 28 publications
9
143
0
5
Order By: Relevance
“…[30] 2-MeSH caused an obvious increase in the hardness of the control and the sample treated with Arg (p < 0.05), suggesting that disulphide bonds were important for the control and the sample treated with Arg. Additionally, the hardness increased by approximately 10% and 41% in the control and sample treated with Arg, respectively, showing that disulphide bonds in the control were less important than those in the sample treated with Arg.…”
Section: S891mentioning
confidence: 97%
See 1 more Smart Citation
“…[30] 2-MeSH caused an obvious increase in the hardness of the control and the sample treated with Arg (p < 0.05), suggesting that disulphide bonds were important for the control and the sample treated with Arg. Additionally, the hardness increased by approximately 10% and 41% in the control and sample treated with Arg, respectively, showing that disulphide bonds in the control were less important than those in the sample treated with Arg.…”
Section: S891mentioning
confidence: 97%
“…[30] PG increased the hardness of the control and the samples treated with Lys or KOH (p < 0.05), suggesting that hydrogen bonds and electrostatic interactions were more Figure 3. Effects of NaSCN, PG, 2-MeSH, or urea on the WHC (A) and hardness (B) of various myosin gel (n = 3).…”
Section: S891mentioning
confidence: 99%
“…It was suggested that acidic subunits had a pI of 4.6-5.4 with a MW of approximately 40,000, whereas basic subunits had a pI of 8.0-8.5 and MW of approximately 20,000 (Nielsen, 1985). Utsumi and Kinsella (1985) suggested that the possible molecular forces involved in the formation of glycinin and β-conglycinin in aqueous solution are hydrogen bonding, hydrophobic associations, ionic interactions and disulphide linkages.…”
Section: Soybean: a Globular Proteinmentioning
confidence: 99%
“…Sesameglobulin was extracted and partially purified according to the procedure described by Yuno-Ohta et al 2,3) Gelation of the proteins was performed by the method of Utsumi et al with slight modifications. 4,5) Aliquots (150 mL) of the 12.5% protein solution in an 80 mM borax buffer (pH 9.2, I ¼ 1:08, the heating buffer) were transferred into glass tubes (60 mm  5 mm i.d.) which were sealed at the bottom with polyvinylidene chloride film and covered at the top with aluminum foil.…”
Section: )mentioning
confidence: 99%